(untitled) (Research, Society and Development, 2021)
Objective: to analyze, from a systematic review of the literature, what are the predictive factors for the development of cardiorrenal syndrome in patients with heart failure. Methods: a systematic review of the literature was performed from the research question "What are the predictive factors for the development of cardiorrenal syndrome in patients with heart failure? For the selection of the articles that compose this study, a search was made in the following databases: Medical Publisher (PUBMED), Virtual Health Library (VHL), Science Direct (SD) and Semantic Scholar, using as eligibility criteria only observational studies or randomized clinical trials that contemplated the research question, which were relevant and current to address the theme. The final sample is composed of 25 publications. Results: the main predictive factors for the development of cardiorrenal syndrome are associated with cardiovascular risk factors and manifestations generated from renal impairment. Conclusion: The junction of comorbidities of the patient, with risk factors for the development of cardiovascular disease, acute renal injury associated with laboratory markers of myocardial injury and renal injury can act as reliable predictive factors for the development of the cardiorrenal syndrome.